Behaviors and perception about academic plagiarism in students of four universities in the city of Arequipa, Peru - Arias-Chávez, Dennis (2020)
Purpose of the study: The purpose of the study aims to describe the behaviors and perceptions of academic plagiarism in university students. Plagiarism is considered one of the most frequent or common ethical problems in the academic community. Under these circumstances, the present study seeks to describe the behaviors and perceptions of academic plagiarism in students from four universities located in the city of Arequipa (Peru). Methodology: For this, a quantitative, descriptive and cross-sectional study was carried out. A structured questionnaire was applied to 1405 students from four universities in Arequipa, enrolled in the first term of the year 2019. Main Findings: The results suggest that the students admit to having committed some of the acts in which plagiarism is recognized in the questionnaire. On the other hand, as to whether the students manage to perceive certain acts as plagiarism, the results indicate that they do so although in a medium degree (“It is almost plagiarism”). Applications of this study: The present study is conducted in university students' academic production, where the students can be exposed and benefitted the importance of academic plagiarism in their works while producing the works. Novelty/Originality of this study: The existing study will assist the university students to correlate more effectively. It is reported that there are marked trends that indicate that the students of the four universities admit to having carried out behaviors amounting to plagiarism; while the acts perceived as plagiarism are related to the management and registration of documentary sources.